Estimating genetic analysis using half diallel cross underlying Kenaf (Hibiscus cannabinus L.) fibre yield in tropical climates - Md Al-Mamun, .; Yusop, Mohd Rafii; Misran, Azizah; Berahim, Zulkarami; Md. Mahmudul Hasan Khan, .; Oladosu, Yusuff (Hindawi, 2022)
Kenaf (Hibiscus cannabinus L.) is a natural fibre crop that can be used for a variety of purposes and has various applications in industry. Despite this, its potential has not been fully exploited because of low yields and a narrow genetic base, limiting hybrids’ development. Based on this background, eight kenaf mutants and one commercial cultivar were selected and crossed in a half-diallel for general and specific combining abilities (GCA and SCA) to get the desired results done in this investigation. The 36 hybrid offspring and their parental lines were tested in the field over two environments. Diallel results based on Griffing B method 2 indicated significant differences for all characters studied except for GCA in top diameter and plant height and top diameter SCA, indicating the existence of both additive and nonadditive gene actions for the inheritance of the traits. The amplitude of GCA variation was much higher than that of SCA variation for all parameters except top diameter and node number, showing the additive gene’s prevalence and the likelihood of genetic advancement through selection. In both conditions, Hayman and Jinks graphical studies demonstrated that partial dominance controlled various fibre yield component parameters such as plant height, middle diameter, stick weight, and fibre weight. On the other hand, fibre yield and the majority of physical features indicated either dominance or overdominance gene action. Plant height, base diameter, core diameter, middle diameter, fresh stem weight, and stick weight all strongly positively correlated with fibre yield. These traits also had a higher proportion of additive effects, a moderate narrow-sense heritability, and a higher baker ratio, indicating successful indirect selection for fibre yield. The parents P1, P3, and P4 had the most dominant alleles for most of the features, while the parents P2, P7, and P9 had the most recessive alleles. The hybrids , , , , , , , , and outperformed the parents in terms of heterotic responses and showed that they have a lot of genetic potential for kenaf enhancement in tropical climates.